Performance on emotional tasks engaging cognitive control depends on emotional intelligence abilities: an ERP study. - Megías-Robles, Alberto; Gutiérrez-Cobo, María José; Gómez-Leal, Raquel; Cabello-González, Rosario; Fernández-Berrocal, Pablo (My University, 2017)
Cognitive control is a key process in decision making and adequately adapting our behavior to the environment. Previous studies have provided evidence of a lower capacity for cognitive control in emotion-laden contexts in comparison with neutral contexts. The aim of the present research was to study changes in cognitive control performance as a function of emotional intelligence (EI) level in contexts involving emotional information. The study sample was composed of 2 groups of 22 participants each: the high and low EI group. Participants carried out an emotional go/no-go task while brain activity was recorded by EEG. N2 and P3 ERPs were used as indices of cognitive control processing. Participants with higher EI showed a larger N2, reflecting a greater capacity for cognitive control related to changes in conflict monitoring, and to a better detection and evaluation of the emotional stimuli. Moreover, in general, response inhibition accuracy was reduced when emotional information was involved in this process. Our findings reveal that neural mechanisms underlying tasks that engage cognitive control depend on emotional content and EI level. This study indicates the important role played by EI in the relationship between emotion and cognition. EI training may be a very useful tool for improving performance in emotion-laden contexts.
Keywords: Inteligencia; Emociones; Elección (Psicología); ERP; Emotional intelligence; Go/no-go tasks